2018
DOI: 10.3390/app8101763
|View full text |Cite
|
Sign up to set email alerts
|

Post-Tensioning Steel Rod System for Flexural Strengthening in Damaged Reinforced Concrete (RC) Beams

Abstract: In this study, a post-tensioning method using externally unbonded steel rods was applied to pre-damaged reinforced concrete beams for flexural strengthening. Nine simply-supported beams, three reference beams and six post-tensioned beams, were subjected to three-point bending. The design parameters observed in this study were the amount of tension reinforcements (3-D19, 4-D19, and 2-D22 + 2-D25; “D” indicates the nominal diameter of the rebar) and the diameters of the external rod (φ22 mm and φ28 mm). A V-shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…The carbon fiber-reinforced polymer (CFRP) has gained popularity for employment in the repair of restoration material for the deteriorated RC structures [5]. The CFRP material is very stiff thus the distinction between the properties of the CFRP sheets and concrete will not favor the transfer of prestressing from the CFRP sheets to RC structure components [11]. Glass fiber-reinforcement polymer (GFRP) sheets have an elasticity Modulus that is close to that of concrete that is why it was selected in the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The carbon fiber-reinforced polymer (CFRP) has gained popularity for employment in the repair of restoration material for the deteriorated RC structures [5]. The CFRP material is very stiff thus the distinction between the properties of the CFRP sheets and concrete will not favor the transfer of prestressing from the CFRP sheets to RC structure components [11]. Glass fiber-reinforcement polymer (GFRP) sheets have an elasticity Modulus that is close to that of concrete that is why it was selected in the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For fire protection, the external tendon is usually covered with a coating, such as metal lath and plaster in the case of systems without ducts. External pre-stressing techniques with steel tendons have been widely used with success to improve existing structures in the United States, Japan, and Switzerland [1][2][3][4][5]. The problem of environmental effects (corrosions, fires, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Taking account of the minimum prestressing 40% of the yield strengths of the external rods, Shin, Lee, and Kang proposed analysis and design methods for an EPT beam with a rectangular section at yield and the ultimate stage for both shored and unshored beams [4]. Lee, Shin, and Lee [12] further investigated the damage of EPT beam due to repetitive loading and concluded that the method was effective in controlling crack width and re-establishing the service load deflections of the beams. Many other researchers have focused on the determination of the stress generated in the external rod during the ultimate flexural failure of the strengthened beam [13][14].…”
Section: Introductionmentioning
confidence: 99%